2018
DOI: 10.1016/j.sjbs.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of two extracts from garlic (Allium sativum L.) cultivars on the human squamous carcinoma cell line SCC-15

Abstract: Garlic (Allium sativum L., Alliaceae) has acquired a reputation as a therapeutic agent and herbal remedy to prevent and treat several pathologies. The aim of the present study was to determine the effect of two Allium sativum L. cultivars, Harnaś and Morado, on reactive oxygen species (ROS) production, viability and apoptotic process in human squamous carcinoma cell line SCC-15. The experiments were conducted on SCC-15 cell line exposed to increasing concentrations of garlic extracts of 0.062, 0.125, 0.250, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…Moreover, in our study, the Chinese and Spanish 'Morado' garlic extracts had the highest antiproliferative effect. A similar effect of the extract from Spanish cultivar 'Morado' was observed in the SCC-15 cell line [Szychowski et al, 2016]. These data suggest that garlic extracts can be toxic to both normal and cancer cells.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, in our study, the Chinese and Spanish 'Morado' garlic extracts had the highest antiproliferative effect. A similar effect of the extract from Spanish cultivar 'Morado' was observed in the SCC-15 cell line [Szychowski et al, 2016]. These data suggest that garlic extracts can be toxic to both normal and cancer cells.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, Polish cultivar 'Harnaś' exhibited an opposite effect on the SCC-15 cancer cell line [Szychowski et al, 2016]. Moreover, in our study, the Chinese and Spanish 'Morado' garlic extracts had the highest antiproliferative effect.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Several garlic extract and its bioactive compounds have been reported for anti-tumour activity with various cancer/tumour cell lines. Szychowski et al 2016 reported the determine the involvement of Reactive Oxygen species (ROS) production in the viability and apoptosis in human tongue squamous carcinoma (SCC-15) cell line after exposure to two Allium sativum L. cultivars, Harnaś and Morado. This study suggested that garlic Polish cultivar Harnaś manifested more prolonged potential to stimulate ROS production in human squamous carcinoma (SCC-15) cells.…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…This study suggested that garlic Polish cultivar Harnaś manifested more prolonged potential to stimulate ROS production in human squamous carcinoma (SCC-15) cells. 9 Yedjou et al 2012 evaluated whether or not garlic extract-induced cytotoxicty and apoptosis in Human Leukemia (HL-60) cells is mediated phyto-constitutents variation in the garlic oil is due to geographic and ecological conditions.…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%